Research Methodology of Action and Technological Innovation on Training Quality in Improving the Capability of Non-Commissioned Soldiers and Enlisted Soldiers of Group 1 Indonesian Army Spesial Force - Adam, Beny; Sadipung, Theresia Oktavia (Dinasti International Journal of Management Science, 2025)
The quality of military training is a key factor in creating soldiers who are well-trained and ready to face various challenges in the field. In the Kopassus environment, known as the elite unit of the Indonesian Army, improving the quality of training is very important considering the complexity of the tasks and missions carried out. In addition, the challenges faced by Kopassus in carrying out its operational missions are increasingly complex, especially with the development of new technologies and tactics. The method used is qualitative. The results of this study are that the current quality of training is considered to require improvement in order to achieve goals, one of which is related to the intellectual and physical abilities of Indonesian Army Special Force Corps soldiers. With the increasing dynamics of global conflict developments, it is necessary to improve the quality of training. There are several aspects that can be improved, including physical, intellectual or scientific and technical. In implementing improvements in the quality of training, it is necessary to implement new things in accordance with current developments by applying action research methods and technological innovation. There are several factors that influence this, including the readiness of resource support and supporting technical instructions.